Nicotinic Acetylcholine Receptor α9 and α10 Subunits Are Expressed in the Brain of Mice - Lykhmus, Olena; Voytenko, Larysa P.; Lips, Katrin S.; Bergen, Ivonne; Krasteva-Christ, Gabriela; Vetter, Douglas E.; Kummer, Wolfgang; Skok, Maryna (Frontiers in Cellular Neuroscience, 2017)
The α9 and α10 nicotinic acetylcholine receptor (nAChR) subunits are likely to be the evolutionary precursors to the entire cys-loop superfamily of ligand-gated ion channels, which includes acetylcholine, GABA, glycine and serotonin ionotropic receptors. nAChRs containing α9 and α10 subunits are found in the inner ear, dorsal root ganglia and many non-excitable tissues, but their expression in the central nervous system has not been definitely demonstrated. Here we show the presence of both α9 and α10 nAChR subunits in the mouse brain by RT-PCR and immunochemical approaches with a range of nAChR subunit-selective antibodies, which selectivity was demonstrated in the brain preparations of α7−/−, α9−/− and α10−/− mice. The α9 and α10 RNA transcripts were found in medulla oblongata (MO), cerebellum, midbrain (MB), thalamus and putamen (TP), somatosensory cortex (SC), frontal cortex (FC) and hippocampus. High α9-selective signal in ELISA was observed in the FC, SC, MO, TP and hippocampus and α10-selective signal was the highest in MO and FC. The α9 and α10 proteins were found in the brain mitochondria, while their presence on the plasma membrane has not been definitely confirmed The α7-, α9- and α10-selective antibodies stained mainly neurons and hypertrophied astrocytes, but not microglia. The α9- and α10-positive cells formed ordered structures or zones in cerebellum and superior olive (SO) and were randomly distributed among α7-positive cells in the FC; they were found in CA1, CA3 and CA4, but not in CA2 region of the hippocampus. The α9 and α10 subunits were up-regulated in α7−/− mice and both α7 and α9 subunits were down-regulated in α10−/− mice. We conclude that α9 and α10 nAChR subunits are expressed in distinct neurons of the mouse brain and in the brain mitochondria and are compensatory up-regulated in the absence of α7 subunits.